The Effect of Prestress on Vibration Behavior of Structures in Impedance Method Damage Detection - Liu, Xianhua; Paurobally, R.; Pan, J. (Trans Tech Publications Inc, 2008)
Structural health monitoring or damage detection has long been a research interest for its great potential for life safety and economic benefits to the industrialized world. Structural vibration behavior is an essential signature of the integrity of structures and hence has been used for damage detection. Structural vibration impedance by way of piezoceramic patch excitation offers a local damage detection technique. It has been known that temperature change has adverse effects on the measured impedance result and can complicate the damage analysis. It is believed that one way of temperature influence on vibration is through adding thermal prestress to the structure. Prestress affects vibration in different ways on different structures and application problems. For the impedance method, prestress comes not only from temperature change but also from other sources such as wind, gravity and working load. This paper deals with prestress effects in the context of local vibration behavior of structures. A theoretical analysis is given on how prestress affects the vibration. Experimental impedance measurement results for piezoceramic patch excited vibration of simple structures such as plates under prestress are presented.